Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/etc.2134
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immunoregulatory genes and its relationship to lead exposure and lead‐mediated oxidative stress in wild ungulates from an abandoned mining area

Abstract: Abstract-Lead (Pb) is a highly toxic metal that can induce oxidative stress and affect the immune system by modifying the expression of immunomodulator-related genes. The aim of the present study was to investigate the association between Pb exposure and the transcriptional profiles of some cytokines, as well as the relationship between Pb exposure and changes in oxidative stress biomarkers observed in the spleen of wild ungulates exposed to mining pollution. Red deer and wild boar from the mining area studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…workers exposed to lead and infertile patients have a high serum level of heavy metals as well as a reduction in sperm parameters (Bonde et al, 2002;Benoff et al, 2009 ). In addition, it has been observed that exposure to lead or mercury caused changes in gene expression of key genes involved in spermatogenesis and antioxidant enzymes ( Rodríguez-Estival et al, 2013;Wanga et al, 2013;Zhang et al, 2016;Xiaozhong et al, 2010;Martinez et al, 2016) . On the other hand, the study of calcium channels in sperms has led to the discovery of four genes, named CatSper 1-4, and two auxiliary proteins, CaSper ß and CatSper ɣ (Darszon et al, 2006) , which have a code for a unique sperm specific cation channel expressed exclusively in the spermatozoa (Qi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…workers exposed to lead and infertile patients have a high serum level of heavy metals as well as a reduction in sperm parameters (Bonde et al, 2002;Benoff et al, 2009 ). In addition, it has been observed that exposure to lead or mercury caused changes in gene expression of key genes involved in spermatogenesis and antioxidant enzymes ( Rodríguez-Estival et al, 2013;Wanga et al, 2013;Zhang et al, 2016;Xiaozhong et al, 2010;Martinez et al, 2016) . On the other hand, the study of calcium channels in sperms has led to the discovery of four genes, named CatSper 1-4, and two auxiliary proteins, CaSper ß and CatSper ɣ (Darszon et al, 2006) , which have a code for a unique sperm specific cation channel expressed exclusively in the spermatozoa (Qi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…В условиях загрязнения сельскохозяйственных угодий соединениями свинца увеличивается вероятность его перехода в продукты питания (мясо, молоко, субпродукты) по трофической цепи почва-растение-животное (1)(2)(3). Свинец обладает высокой кумулятивной способностью и в зависимости от дозы и продолжительности воздействия на млекопитающих проявляет высокую общую токсичность, эмбриотоксичность, канцерогенность и генотоксичность (4)(5)(6). Всемирная организация здравоохранения (ВОЗ, World Health Organization, WHO) установила предельно допустимое поступление свинца в организм человека в количестве 25 мкг•кг 1 массы тела в неделю, или 3,6 мкг•кг 1 массы тела в сутки.…”
unclassified